The application of agricultural wastes for heavy metals adsorption: A meta-analysis of recent studies - Muhammad, Imran-Shaukat; Rafeah, Wahi; Zainab, Ngaini (Elsevier Ltd., 2021)
Numerous studies have been carried out to investigate the suitability of various agricultural wastes as biosorbent for heavy metals removal. Previous published reviews on heavy metal removal by agricultural waste-based biosorbent were limited to narrative and systematic reviews, with no statistical analysis to compare outcomes across different biosorbents sources. In this work, meta-analysis technique was applied to identify gaps in contemporary biosorbents research. A meta-analysis was undertaken using several packages of R programme on publications over the last five years to evaluate the capability of eleven different types/components agricultural wastes for the adsorption of eight heavy metal. Based on the findings, agricultural wastes have the potential to be employed for heavy metal adsorption from aqueous media in general. However, the disparities in the findings suggest that when utilising different types of raw biomass as adsorbents, modifying the biomasses into carbonenriched forms would be a preferable option.